ANALYSIS OF INTENTION TO USE SHARIA DIGITAL BANKING USING TAM 3 AND UTAUT THEORY - Niniek Adenia; Alifia Nur Zaida; Hasanah Listiyanti (Universitas Airlangga, 2022)
Digital banking is an innovation in the banking sector that allows customers to make financial transactions more easily. The use of digital banking in Indonesia is inseparable from the very massive penetration of mobile devices, where the number reaches 355.5 million. Over time, digital banking began to be developed by adjusting to sharia principles. One of the sharia-based platforms from PT. Jago Bank Tbk. is become a breakthrough for the growth of sharia digital banking in Indonesia. The platform was just launched in the first quarter of 2022 and it can make an optimal contribution to financing. This condition indicates that there is an opportunity for sharia digital banking to continue to grow. The realization of this development was partly driven by the good acceptance of a technology-based platform. The existence of good technology acceptance can influence someone's intention to start using the offered digital platform. This study aims to analyze the factors that influence individual intentions to use sharia digital banking at Bank Jago Syariah. This study uses a quantitative approach where data is obtained by distributing questionnaires to generation Z by adopting the TAM 3 and UTAUT theories. Tests were carried out by adopting the SEM-PLS model using the Warp PLS 5.0 data analysis tool. The implementation of this research is expected to be able to optimize sharia digital banking which will then contribute to the development of the Islamic economy in Indonesia.